The Rare Five-Spot Ladybird Coccinella quinquepunctata (Coleoptera: Coccinellidae) Surviving in an Unstable Habitat - Farrow, Rachel A.; Roy, Helen E.; Brown, Peter M. J. (Frontiers in Conservation Science, 2022)
Coccinella quinquepunctata (the five-spot ladybird), was considered extinct in the UK until 1987. It is classified as (RDB3) Rare, mainly as a result of its preferred habitat; exposed riverine sediment. This habitat is in a constant state of alteration and the quality of the habitat is being degraded to the point that specialised invertebrate species, such as C. quinquepunctata, are at risk. In recent years, the rapid spread of the invasive alien Harmonia axyridis (harlequin ladybird) has been linked to a decline in native coccinellid numbers. There is concern that the narrow habitat requirements of C. quinquepunctata, together with the continuing spread of H. axyridis, will result in a decline in the abundance of C. quinquepunctata. Two habitat types (exposed riverine sediment and grassland) along 12 Welsh rivers were surveyed for C. quinquepunctata, H. axyridis and other coccinellids. When an individual coccinellid was recorded, so too was its elevation from the substrate. Plant species that C. quinquepunctata were observed on and vegetation density on the shingle were assessed in broad categories. Of all recorded coccinellids, 76% were C. quinquepunctata while 7% were H. axyridis. A third of the sites had no records of H. axyridis. A significantly greater number of C. quinquepunctata were observed within 0.5 metres of the exposed riverine sediment rather than higher up on the vegetation. Presence of the invasive plant Himalayan balsam (Impatiens glandulifera) may have a negative effect on C. quinquepunctata. These findings indicate that intraguild predation is unlikely to occur given the low abundance of H. axyridis in C. quinquepunctata habitat. However, the unstable nature of exposed riverine sediment, and a combination of threats from invasive alien species indicates that this species is still at risk of sudden decline and requires further monitoring and conservation efforts.